(untitled) (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
In the past few decades, biodegradable polymers obtained from natural resources (such as chitosan, starch, sodium alginate, cellulose, gelatin, etc.) are replacing non-degradable plastics to prevent the further degradation of the environment. Thus, the present study focuses on the synthesis of biodegradable nanocomposites (NCs) using the blend of Starch (St) and Sodium Alginate (SA) as matrix and copper (core)-silver (shell) nanoparticles (NPs) as nanofillers as their distinctive surface plasmon resonance (SPR) band is observed within 350 nm-700 nm i.e. in the visible region. For the present study, Cu (core)-Ag (shell) NPs synthesized via a chemical reduction approach were used to fabricate biodegradable Cu-Ag@St-SA NC films via the solution casting technique. The morphological studies of the prepared core-shell NPs were performed using Transmission Electron Microscope (TEM). The size of the Cu-Ag core-shell NPs obtained from TEM comes out to be 18.5±3.0 nm. The NC films were further characterized by UV-Visible spectrophotometer and the data obtained was analyzed to determine Urbach’s energy ‘Eu’, optical energy gap ‘Eg’, optical conductivity ‘σopt’, and refractive index ‘n’. The value of ‘Eg’ for Starch-SA is found to decrease from 4.39 eV to 2.05 eV for 0.48 wt% Cu-Ag@St-SA NC film and ‘Eu’ increases from 1.04 eV for Starch-SA to 3.03 eV for 0.48 wt% Cu-Ag@St-SA NC film. The NC film containing 0.48 wt% Cu-Ag NPs blocks the UV radiations and thus, can be employed as a UV filter in various devices.